One-pot Selective Conversion of Biomass-derived Furfural into Cyclopentanone/Cyclopentanol over TiO2 Supported Bimetallic Ni-M (M = Co, Fe) Catalysts - Maria Dewi Astuti; Ditya Kristina; Rodiansono Rodiansono; Dwi Rasy Mujiyanti (Bulletin of Chemical Reaction Engineering & Catalysis, 2020)
One-pot selective conversion of biomass-derived furfural (FFald) into cyclopentanone (CPO) or cyclopentanol (CPL) using bimetallic nickel-based supported on TiO2 (denoted as Ni-M(3.0)/TiO2; M = Co and Fe; 3.0 is Ni/M molar ratio) have been investigated. Catalysts were synthesized via a hydrothermal method at 150 °C for 24 h, followed by H2 reduction at 450 °C for 1.5 h. X-ray Diffraction (XRD) analysis  showed that the formation of Ni-Co alloy phase at 2θ = 44.2° for Ni-Co(3.0)/TiO2 and Ni-Fe alloy at 2θ = 44.1° for Ni-Fe(3.0)/TiO2. The amount of acid sites was measured by using ammonia-temperature programmed desorption (NH3-TPD). Ni-Co(3.0)/TiO2 has three NH3 desorption peaks at 180 °C, 353 °C, and 569 °C with acid site amounts of 1.30 µmol.g-1, 1.0 µmol.g-1, and 2.0 µmol.g-1,        respectively. On the other hand, Ni-Fe(3.0)/TiO2 consisted of NH3 desorption peaks at 214 °C and 626 °C with acid site amounts of 3.3 µmol.g-1and 2.0 µmol.g-1, respectively. Both Ni-Co(3.0)/TiO2 and Ni-Fe(3.0)/TiO2 catalysts were found to be active for the selective hydrogenation of FFald to furfuryl alcohol (FFalc) at low temperature of 110 °C, H2 3.0 MPa, 3 h with FFalc selectivity of 81.1% and 82.9%, respectively. High yields of CPO (27.2%) and CPL (41.0%) were achieved upon Ni-Fe(3.0)/TiO2 when the reaction temperature was increased to 170 °C, 3.0 MPa of H2, and a reaction time of 6 h. The yield of CPO+CPL on the reused catalyst decreased slightly after the second reaction run, but the activity was maintained for at least three consecutive runs. Copyright © 2020 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).